Handbook of research on cross-disciplinary uses of gamification in organizations - Bernardes, Oscar, 1978-; Amorim, Vanessa, 1992-; Moreira, António Carrizo (Advances in business strategy and competitive advantage., 2022)
"This book looks at the field of Gamification for economic and social development while providing for further research opportunities in this dynamic and growing field with the goal of increasing the understanding of the importance of Gamification in the context of organizations' improvements, providing relevant academic work,and empirical research findings"--